An analysis of the crises’ cyclicity in the market economy - BALU, Mariana Elena (Annals of Spiru Haret University. Economic Series, 2012)
The social-economic phenomena and processes have a cyclical character, which falls within the natural development of the economic activity. Periodically, national economies or certain economic branches are affected by states of crisis, of unbalance, which disrupt the normal course of the economic activity and development. The occurrence of fluctuations in the economic field gives birth to economic cycles, defined as the time separating two economic or financial crises. Crises represent a deregulation, a sudden disorder of the economic balance, but they are necessary in the sense that they “are an indispensable sanction of management errors” and the problem is not the elimination of all crises, but only of those which “weigh heavily on the economic activity and are a systemic risk”. The main causes of an economic crisis are of a political, social or financial nature. Romania has been affected by the crisis at the commercial level, its exports being reduced and at the financial level, by the limitation of the access to external financing, reflected in the depreciation of the domestic currency. The analysis of the Balance of External Payments (BEP) in the period January-October 2011, shows that the deficit of current account of the BEP was of 4,097 million Euros, having fallen by 9.5% comparing to the same period of 2010, a situation explained by the reduction of the trade deficit by 12.7%.